2021
DOI: 10.2217/fca-2020-0237
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant Myocarditis: Covid Or Not COVID? Reinfection Or co-infection?

Abstract: We describe a unique case of fulminant myocarditis in a patient with presumed SARS-CoV-2 reinfection. Patient had initial infection 4 months backand had COVID-19 antibody at the time of presentation. Endomyocardial biopsy showed lymphocytic myocarditis, that is usually seen in viral myocarditis. The molecular diagnostic testing of the endomyocardial biopsy for cardiotropic viruses was positive for Parvovirus and negative for SARS-CoV-2. Authors highly suspect co-infection of SARS-CoV-2 and Parvovirus, that pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…We reported a case of fulminant myocarditis, confirmed by CMR, in a young COVID-19-positive patient. Should we have not sent the sample for a viral genome, we would have little doubt that the myocarditis was due to COVID-19; however, the genome test returned positive for parvovirus [21]. This observation is not unique.…”
Section: Discussionmentioning
confidence: 92%
“…We reported a case of fulminant myocarditis, confirmed by CMR, in a young COVID-19-positive patient. Should we have not sent the sample for a viral genome, we would have little doubt that the myocarditis was due to COVID-19; however, the genome test returned positive for parvovirus [21]. This observation is not unique.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, the cardiac Society of Australia and New Zealand 94 and the American Society for Artificial Internal Organs 95 suggested that Impella could be considered for a selected subgroup of COVID‐19 patients suffering acute cardiac failure without severe respiratory failure (Table 4). However, few clinical reports are now emerging regarding the use of this device, and they indicate that Impella alone might not be enough to support these patients often affected by biventricular failure and hypoxia 72,75,78 . Contrarily, it seems more effective as left ventricular unloading combined with V‐A ECLS 72,75,77,78 or circulatory support associated with V‐V ECLS 72 …”
Section: Discussionmentioning
confidence: 99%
“…There are numerous indications for a contribution of B19V co-infections for the progression to myocardial injury. Thus, B19V-induced cardiac damage could be enhanced by coinfection with other viral species, such as HHV6, influenza or even SARS-CoV-2 [109][110][111][112]. For instance, a recent autopsy report from a 5-year-old girl revealed that co-infection of myocardial B19V with respiratory influenza virus can cause fulminant myocarditis and pneumonia [109].…”
Section: Erythroparvovirusmentioning
confidence: 99%
“…Importantly, SARS-CoV-2 might also play a role in the pathogenesis of autoimmune myocarditis. Co-infection of SARS-CoV-2 and B19V is furthermore suggested to trigger the immune cascade resulting in fulminant myocarditis [110].…”
Section: Sars-cov-2mentioning
confidence: 99%